Localized Myxofibrosarcomas: Roles of Surgical Margins and Adjuvant Radiation Therapy - Boughzala-Bennadji, Raoudha; Stoeckle, Eberhard; Le Péchoux, Cécile; Méeus, Pierre; Honoré, Charles; Attal, Justine; Duffaud, Florence; De Pinieux, Gonzague; Bompas, Emmanuelle; Thariat, Juliette; Leroux, Agnès; Bertucci, François; et al. (International journal of radiation oncology, biology, physics, 2018)
The objective of this study was to describe the outcome and prognostic factors for adults treated for localized myxofibrosarcoma. We conducted a retrospective multicenter study of 425 nonmetastatic patients who underwent surgery between January 1996 and December 2015 in French National Group and were enrolled in the Conticabase. Pathologic diagnosis was systematically reviewed by expert pathologists. The endpoints were relapse-free and metastasis-free survival. Log-rank tests and Cox models have been used to identified prognostic factors. Median age was 66 years; 53% were males; 85% of cases occurred in limbs or superficial trunk; median size was 60 mm; 47% and 39% were grades 2 and 3, respectively; 66% had R0 resection and 34% R1 resection. Adjuvant radiation therapy was given to 65% of patients, neoadjuvant radiation therapy to 3%, neoadjuvant chemotherapy to 7%, and adjuvant chemotherapy to 13%. The median follow-up was 51 months. The 5-year local relapse-free survival was 67%; independent prognostic factors for local relapse were R1 resection (hazard ratio [HR] = 1.26; P = .001) and adjuvant radiation therapy (HR = 0.35; P = .0001) (ie, R1 resection and no adjuvant radiation therapy increase the hazard ratio). In stratified analysis, adjuvant radiation therapy was beneficial after R0 resection (P = .0020) and after R1 resection (P = .0001). The 5-year overall survival was 80%. The 5-year metastasis-free survival was 83%. Independent prognostic factors for metastatic relapse were grade 3 disease (HR = 1.975; P = .0001) and tumor size (HR = 1.006; P = .001). This large series of myxofibrosarcoma confirms the high rate of local relapse. Combination of R0 resection and adjuvant radiation therapy provided the best local control. In parallel with an increasing rate of R0 resection and adjuvant radiation therapy, we observed a constant improvement in both metastatic and local relapse-free survival during the study.